Development of Quizizz Application-Based Assessment to Measure Reasoning Ability of Middle School Students' on Flat Shape Materials - Elfrida Rahmasari; Mohammad Syaifuddin; Rizal Dian Azmi (Department of Mathematics Education University of Muhammadiyah Malang, 2022)
This research is development research that aims to develop an assessment based on the Quizizz application to measure the reasoning ability of junior high school students' flat wake material. The research subjects were 60 junior high school students. Data sources were obtained from the results of the test and student response questionnaires. The steps for adopting test development using the Djemari Mardapi stage with the following steps: compiling test specifications, writing tests, reviewing tests, conducting test trials, analyzing test items, refining tests, assembling tests, administering tests, and interpreting test results. The results showed that the Quiziz application-based assessment was valid, reliable, practical, and effective. The test has a characteristic difficulty level, namely two easy category questions and eight medium category questions, and the distinguishing power of 8 very good questions and two good questions. The reasoning ability of students' flat shapes, as measured by an assessment based on the Quizizz application, has an average of 67.83, with a fairly good category.